2022
DOI: 10.1021/acs.nanolett.1c04562
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activation of T-Cell Proliferation by Regulating Cell Surface Receptor Clustering Using a pH-Driven Interlocked DNA Nano-Spring

Abstract: Activation of T-cell proliferation specifically in a tumor is crucial for reducing the autoimmune side effects of antitumor immunotherapy. Herein, we developed a pH-driven interlocked DNA nano-spring (iDNS) to stimulate T-cell activation in vivo in response to the low pH value in a tumor microenvironment. The interlocked structure of iDNS provide a more rigid scaffold in comparison to double-stranded DNA for ligand assembly, which can help to control the spatial distribution of ligands with more accuracy. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…After binding, the aminated fullerene complex initiates the transfer of cytoplasmic myosin heavy chain 9 to the cell edge, thereby inhibiting cancer cell migration and the epithelial-to-mesenchymal transition process. 107 Kosuke Minami and co-workers have developed water-soluble cationic fullerenes, tetra-( piperazino) [60]fullerene epoxide-serum protein ternary complexes, for the effective delivery of highly unstable siRNA. The amphiphilic nature of the fullerene complex and its conjugation with protein forms a stable micelle that protects siRNA for safer delivery at the target site.…”
Section: Fullerene Nanoarchitectonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After binding, the aminated fullerene complex initiates the transfer of cytoplasmic myosin heavy chain 9 to the cell edge, thereby inhibiting cancer cell migration and the epithelial-to-mesenchymal transition process. 107 Kosuke Minami and co-workers have developed water-soluble cationic fullerenes, tetra-( piperazino) [60]fullerene epoxide-serum protein ternary complexes, for the effective delivery of highly unstable siRNA. The amphiphilic nature of the fullerene complex and its conjugation with protein forms a stable micelle that protects siRNA for safer delivery at the target site.…”
Section: Fullerene Nanoarchitectonicsmentioning
confidence: 99%
“…They found that the developed system is more stable than that of double-stranded DNA, which regulates the nanoscale distribution of the cluster of differentiation (CD3) receptor on the cell surface at low pH (tumor microenvironment). 60 In another study, pheophorbide A photosensitizers were grafted on a DNA backbone using phosphorothioate modification and small inhibitory RNAs (siRNA) along with a programmed death ligand were pooled together to form a supramolecular structure via self-assembly. The developed tetrahedron network was able to kill cells through photodynamic activity and simultaneously silence programmed death ligand expression for enhanced antitumor activity.…”
Section: Materials Nanoarchitectonics: a Paradigm Shift To Create Bio...mentioning
confidence: 99%
“…3c). 62 By encoding a cytosine-rich i-motif structure in interlocked circular DNA nanostructures, a spring-like shrinking was achieved in response to the relatively low pH value in tumors to regulate the nanoscale distribution of T-cell receptors (CD3) on the cell surface. This platform elicited significant T-cell proliferation and subsequently enhanced the antitumor effect.…”
Section: Ph-responsive Strategymentioning
confidence: 99%
“…T cell-based immunotherapy has received great attention in tumor treatments ( Zhang, K. et al, 2022 ) in recent years. Engineering T cells is a rapidly advancing technology and is a good strategy for stimulating T cells proliferation to effectively target tumors ( Belk et al, 2022 ).…”
Section: Potential Therapeutical Alternatives For Postpartum Depressi...mentioning
confidence: 99%